2018
DOI: 10.2174/1381612823666170725142337
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid-lowering Effects and Associated Mechanisms of Dietary Phytosterol Supplementation

Abstract: Phytosterols (PS) are plant-based structural analogous of mammalian cholesterol that have been shown to lower blood cholesterol concentrations by ~10%, although inter-individual response to PS supplementation due to subject-specific metabolic and genetic factors is evident. Recent work further suggests that PS may act as effective triglyceride (TG)-lowering agents with maximal TG reductions observed in hypertriglyceridemic subjects. Although PS have been demonstrated to interfere with cholesterol and perhaps T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 104 publications
1
37
0
1
Order By: Relevance
“…Some phytosterols may be added to food (usually margarine), and they compete with cholesterol as regards intestinal absorption and can thereby lower LDL cholesterol [38]. It has been reported that phytosterols reduce LDL levels and increase HDL in the blood and, thus, have a potential place in the treatment of hyperlipidaemia [39,40,41]. A potential source of the phytosterols in the present study could be the yeast in the tablets containing yeast selenium.…”
Section: Discussionmentioning
confidence: 98%
“…Some phytosterols may be added to food (usually margarine), and they compete with cholesterol as regards intestinal absorption and can thereby lower LDL cholesterol [38]. It has been reported that phytosterols reduce LDL levels and increase HDL in the blood and, thus, have a potential place in the treatment of hyperlipidaemia [39,40,41]. A potential source of the phytosterols in the present study could be the yeast in the tablets containing yeast selenium.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism of action involved in lowering the cholesterol is that it increases the faecal excretion of cholesterol by reducing the absorption of it. Also, it lowers the triglyceride levels in liver and plasma, both 56 . Another study also revealed the mechanism of phytosterol action as inhibiting the absorption of cholesterol and increase excretion of it 57 .…”
Section: Pharmacological Potentials Of Moringa Oleiferamentioning
confidence: 98%
“…Numerous studies have been reported that β-sitosterol administration has the potential to reduce cholesterol levels (Sugano et al, 1977;Lei et al, 2017;Suganya et al, 2017). Its cholesterol-reduction mechanism has several theories, but the most widely proposed was to reduce dietary cholesterol absorption and interfere with intestinal transport (Dumolt and Rideout, 2018). Furthermore, the reduction of dietary cholesterol absorption is possible due to the cholesterol displacement by β-sitosterol in bile acid micellar formation (Jesch and Carr, 2006), thereby limiting cholesterol uptake in the small intestine and increasing fecal excretion.…”
Section: Figure 3: the Ghmbcad Correlations Of Compoundmentioning
confidence: 99%